Thorium- and Uranium-Mediated C-H Activation of a Silyl-Substituted Cyclobutadienyl Ligand - Tsoureas, Nikolaos; Rajeshkumar, Thayalan; Townrow, Oliver P.E.; Maron, Laurent; Layfield, Richard A. (Inorganic Chemistry, 2022)
Cyclobutadienyl complexes of the f-elements are a relatively new yet poorly understood class of sandwich and half-sandwich organometallic compounds. We now describe cyclobutadienyl transfer reactions of the magnesium reagent [(η4-Cb'''')Mg(THF)3] (1), where Cb'''' is tetrakis(trimethylsilyl)cyclobutadienyl, toward thorium(IV) and uranium(IV) tetrachlorides. The 1:1 stoichiometric reactions between 1 and AnCl4proceed with intact transfer of Cb'''' to give the half-sandwich complexes [(η4-Cb'''')AnCl(μ-Cl)3Mg(THF)3] (An = Th, 2; An = U, 3). Using a 2:1 reaction stoichiometry produces [Mg2Cl3(THF)6][(η4-Cb'''')An(η3-C4H(SiMe3)3-κ-(CH2SiMe2)(Cl)] (An = Th, [Mg2Cl3(THF)6][4]; An = U [Mg2Cl3(THF)6][5]), in which one Cb'''' ligand has undergone cyclometalation of a trimethylsilyl group, resulting in the formation of an An-C σ-bond, protonation of the four-membered ring, and an η3-allylic interaction with the actinide. Complex solution-phase dynamics are observed with multinuclear nuclear magnetic resonance spectroscopy for both sandwich complexes. A computational analysis of the reaction mechanism leading to the formation of 4 and 5 indicates that the cyclobutadienyl ligands undergo C-H activation across the actinide center. copy; 2022 American Chemical Society.